Who is the Native of the Sarvasiddhāntatattvacūḍāmaṇi? - Sarma, Sreeramula Rajeswara (History of Science in South Asia)

(untitled) (University of Alberta Library, 2021)
The British Library, London, holds a unique manuscript copy of a Sanskrit text entitled Sarvasiddhāntatattvacūḍāmaṇi (MS London BL Or. 5259). This manuscript, consisting of 304 large-size folios, is lavishly illustrated and richly illuminated. The author, Durgāśaṅkara Pāṭhaka of Benares, attempted in this work to discuss all the systems of astronomy – Hindu, Islamic and European – around the nucleus of the horoscope of an individual personage. Strangely, without reading the manuscript, the authors Sudhākara Dvivedī in 1892, C. Bendall in 1902 and J. P. Losty in 1982, declared that the horoscope presented in this work was that of Nau Nihal Singh, the grandson of Maharaja Ranjit Singh of Lahore, and this has been the prevailing notion since then. The present paper refutes this notion and shows – on the basis of the relevant passages from the manuscript – that the real native of the horoscope is Lehna Singh Majithia, a leading general of Maharaja Ranjit Singh.